Distinct functions of ventral CA1 and dorsal CA2 in social memory - Watarai, Akiyuki; Tao, Kentaro; Wang, Mu-Yun; Okuyama, Teruhiro (Current opinion in neurobiology, 2021)
For animals that live in social groups, the ability to recognize conspecifics is essential. Recent studies of both human patients and animal models have vigorously sought to discern the precise mechanisms by which hippocampal neurons and neural circuits contribute to the encoding, consolidation, storage, and retrieval of social memory. In particular, optogenetic manipulation enables us to investigate the presence of memory engrams. We recently revealed the presence of social memory engrams in hippocampal ventral CA1 neurons, using optogenetic manipulation and calcium (Ca2+) imaging. In the present manuscript, we discuss the current viewpoints on two hippocampal subregions in regards to social memory representation, namely dorsal CA2 for information processing and ventral CA1 for the storage of social memory, specifically from the perspectives of behavioral neuroscience and neurophysiology.